2014
DOI: 10.1021/es504088e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chromatographic Separation of Dissoluble Ag(I) and Silver-Containing Nanoparticles of 1–100 Nanometer in Antibacterial Products and Environmental Waters

Abstract: Sensitive and rapid methods for speciation analysis of nanoparticulate Ag (NAg) and Ag(I) in complex matrices are urgently needed for understanding the environmental effects and biological toxicity of silver nanoparticles (AgNPs). Herein we report the development of a universal liquid chromatography (LC) method for rapid and high resolution separation of dissoluble Ag(I) from nanoparticles covering the entire range of 1−100 nm in 5 min. By using a 500 Å poresize amino column, and an aqueous mobile phase contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 50 publications
2
89
0
1
Order By: Relevance
“…The quantification process using CE-ICPMS was first evaluated on multiple types of Ag NPs. Several previous studies have reported size-dependent signal response of nanoparticles in ICPMS, which can be explained by the variation in the nebulization efficiency [9,26]. We first spiked BGE with 30 μg kg −1 of CA coated Ag nanoparticles in different sizes to investigate their signal response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification process using CE-ICPMS was first evaluated on multiple types of Ag NPs. Several previous studies have reported size-dependent signal response of nanoparticles in ICPMS, which can be explained by the variation in the nebulization efficiency [9,26]. We first spiked BGE with 30 μg kg −1 of CA coated Ag nanoparticles in different sizes to investigate their signal response.…”
Section: Resultsmentioning
confidence: 99%
“…Several liquid chromatographic methods have been developed for the speciation of nanoscale silver [9,10]. By using ICPMS as the detection method, LODs can easily reach a sub μg kg −1 level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles technology is applied to a wide range of products in the fields of cosmetics, biomedicine, food and food packaging, bioremediation, coatings, electronics, catalysis and material sciences, among many others (Nel et al, 2006) (Christensen et al, 2010) (Nowack et al, 2011(Nowack et al, ) (2016. Particularly, silver nanoparticles (AgNPs) are used in consumer products due to a proved antimicrobial properties attributable to the release of Ag + (Zhou et al, 2014) (Xiu et al, 2012). Because of the massive and uprising tendency to use NPs in general and Ag-NPs in particular (Nowack et al, 2011), the release of nano-residues into different compartments in the environment should be taken into account (López-Serrano et al, 2014) (Schaumann et al, 2015), being water bodies particularly at risk, as they act as a sink for most environmental contaminants (Farré et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, analytical scientists are dedicating efforts to develop selective, robust and reliable fit-for-purpose methods that are able to separate, isolate and measure NPs to characterise the number based-particle size distribution (PSD). To date, Asymmetric Flow Field Flow Fractionation (AF4) (Poda et al, 2011) (Loeschner et al, 2013) (Mitrano et al, 2012a), chromatographic techniques (Zhou et al, 2014) and filtration (Mitrano et al, 2015) are among the most frequently used techniques to separate NPs, often coupled to light scattering, UV or Inductively Couple Plasma Mass Spectrometry (ICP-MS) detectors (Barahona et al, 2016) (Cascio et al, 2014). Each measuring technique and approach exhibits its own advantages and limitations and a combined use of all of them following a multimethod approach has been sometimes proposed since the information from each individual method is usually complementary ( Hagendorfer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%